'... allein ein Ganzes ist es nicht': Schumann's Szenen aus Goethes Faust. (June 2014) - Lamport, Francis
<x content-type="archive" xml:space="preserve">Abstract</x> Schumann was ahead of his time in choosing to set scenes from Part II of Goethe's Faust, which was little appreciated at the time; but the theme of redemption held a particular attraction for him. Accordingly, he began by setting the final 'Bergschluchten' scene as a kind of oratorio, then worked back and added two prefatory sections in more dramatic style, based on scenes from Goethe's Parts I (Gretchen scenes) and II (Acts I and V). The Overture was composed last of all. The Scenes are discontinuous and allusive, and the musico-dramatic nature of the whole and the relative merits of the three sections are still a matter of critical disagreement.